Early Canadiana on the World Wide Web: Preliminary Analysis of Usage Patterns and Usage Feedback - Cherry, Joan M.; Duff, Wendy M.; Oxford, Gerry (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Early Canadiana Online (ECO) is a full-text, Web-based collection of pre-1900 documents which were published in Canada, or which were published in other countries but written by Canadians or about Canada. This paper reports preliminary findings from two studies of this collections- one involving software monitoring of usage of the collection; the other involving a Web-based user survey.